Utilização de hidroretentor em substrato semi-saturado na produção de mudas de eucalipto - Vervloet Filho, Radagasio Hugo (2011)
This study aimed at testing the addition of three different doses of gel (soil Hydroretainer) in the production of hybrid seedlings of E. grandis X E. urophylla in two different water samples. Four clones were used (6437, 6466, 11420 and 11436). The study was conducted in nurseries at Fibria S.A., in the municipality of Aracruz - Espírito Santo. The parameters for assessing the development of seedlings occurred in four main phases of production: rooting, acclimation, growth and rustication. During these phases were monitored the moisture content of the substrate, cuttings rooting, plant survival, height growth of the bud, diameter growth of the base of the stem, nutritional status, water potential of plants leaves and ratings of the quality standard of the plants produced. With these results, it was not possible to conclude what the optimal dosage of the polymer hidroretentor to be used because the experiment was conducted in semi-saturated substrate. It was concluded that reducing the water level did not impair plant development. In addition, we evaluated the quality of the seedlings at the time of shipment and found that the better performance of clones 6437 and 6466